2001
DOI: 10.1046/j.1365-8711.2001.04754.x
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniform extinction in young open star clusters

Abstract: The extinction law and the variation of colour excess with position, luminosity as well as spectral class in young open star clusters NGC 663, NGC869, NGC 884, NGC 1502, NGC 1893, NGC 2244, NGC 2264, NGC 6611, Tr 14, Tr 15,Tr 16, Coll 228, Tr 37 and Be 86 have been studied. The difference in the minimum and maximum values of E(B-V) of cluster members has been considered as a measure of the presence of non-uniform gas and dust inside the clusters. Its value ranges from 0.22 to 1.03 mag in clusters under study, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 40 publications
6
49
0
Order By: Relevance
“…Indeed, as shown by, e.g. Yadav & Sagar (2001), the differential reddening tends to increase towards younger ages, in some cases reaching ΔE(B − V) ≈ 1 mag, or ΔA V ≈ 3 mag. Since we cannot derive the extinction for individual stars with 2MASS photometry, we examine the effect of differential reddening simply by means of a reddening vector (Figs.…”
Section: Derivation Of Fundamental Parametersmentioning
confidence: 66%
“…Indeed, as shown by, e.g. Yadav & Sagar (2001), the differential reddening tends to increase towards younger ages, in some cases reaching ΔE(B − V) ≈ 1 mag, or ΔA V ≈ 3 mag. Since we cannot derive the extinction for individual stars with 2MASS photometry, we examine the effect of differential reddening simply by means of a reddening vector (Figs.…”
Section: Derivation Of Fundamental Parametersmentioning
confidence: 66%
“…(3) Sodium is known to be only a fair tracer of dust, and our low-resolution spectra do not resolve the individual absorption systems that contribute to the Na i D lines, making it impossible to estimate the effect of line saturation. (4) and (5) The reddening along the specific line of sight to SN 1999gi may differ from the average reddening to the OB association and/or the reddening to specific association members (see, e.g., Yadav & Sagar 2001). Nonetheless, taken together the general agreement of all the estimates makes a compelling case for low reddening to SN 1999gi, with E(BÀV ) = 0.20 mag (comparison with SN 1999em); 0.25 mag (Na i D absorption); 0.15 mag (reddening to OB association); and 0.34 (reddening to H ii region), and an upper reddening limit of E(BÀV ) < 0.45 mag coming from the analysis of the early-time continuum shape.…”
Section: The Reddening Of Sn 1999gimentioning
confidence: 99%
“…They show that Berkeley 86 is isolated and projected against an area totally free of gas and dust, which is indicative of low levels of extinction for this cluster. Yadav & Sagar (2001) found that Berkeley 86 suffers non-uniform reddening with colour-excess varying in the range 0.24 < E(B − V) < 1.01, while Forbes (1981) measured a more uniform estimation of E(B − V) = 0.96 ± 0.07. NGC 2244 is located at the centre of the Rosette Nebula.…”
Section: Selected Clustersmentioning
confidence: 98%
“…According to Yadav & Sagar (2001), the correct identification of members is crucial for the assessment of extinction in the direction of the cluster and the most reliable selection is based on kinematic studies (proper motion and radial velocity). DAML02 provides a list of stars with JHK photometry -2MASS catalogue (Cutri et al 2003) -and also the probability of the star belonging to the cluster (P%), which is determined from its proper motion.…”
Section: Data Extraction and Cluster Membershipmentioning
confidence: 99%
See 1 more Smart Citation